Insulin therapy waste produced in the households of people with diabetes monitored in Primary Care - Gilmara Holanda da Cunha; Raiza Verônica Almeida Barbosa; Marina Soares Monteiro Fontenele; Maria Amanda Correia Lima; Katia Barbosa Franco; Francisco Vagnaldo Fechine
ABSTRACT Objective: To analyze the insulin therapy waste disposal produced in the households of people with diabetes mellitus (DM). Method: Cross-sectional study with 105 Primary Care patients. Socio-demographic and clinical variables and insulin therapy practice were analyzed through the absolute and relative frequencies, Fisher's exact test and prevalence ratio (PR). Results: The association between types of insulin (60.0%), administered with a disposable syringe attached to a needle (80.9%), and a high percentage of reuse and disposal in normal household waste (57.1%) stood out. The professionals who most frequently provided guidance to people with diabetes were the nurses. Patients who had received instructions about disposal were 21 times more likely to dispose of waste properly than those who had not (PR 21.5; P < 0.0001). Age, gender, skin color, education, marital status, occupational status and type of DM did not interfere in the disposal (P > 0.05). Conclusion: People with diabetes served in Primary Health Care require guidance and material resources to carry out the appropriate disposal of insulin therapy waste.